SECONDARY BLADDER CARCINOMA METASTASIS FROM OTHER ORGAN: A LITERATURE REVIEW - Wahyudi, Yuvi; Mustafa, Akhmad (Indonesian Journal of Urology, 2025)
Objective: This review article discusses the importance of considering metastasis malignancy in the differential diagnosis of high-grade urothelial lesions. Material & Methods: The review presents a summary of metastasis of bladder carcinoma from various organs. The most common sources of secondary bladder tumors are stomach, breast, colon cancer, and melanoma. The article highlights the need for careful evaluation and further workup in patients being treated for metastatic cancer who present with hematuria and symptomatic anemia. Results: Diagnosis of secondary bladder carcinoma involves imaging, cystoscopy, and transurethral resection. Biopsies should be collected from patients with suspected urothelial bladder metastasis from other cancer origins or those with suggestive symptoms. The article emphasizes the importance of differentiating metastatic adenocarcinoma of the lung from primary bladder adenocarcinoma, especially when bladder examination does not correlate with imaging results. It also discusses the increased risk of secondary bladder carcinoma in rectal cancer survivors who have undergone radiation therapy. Conclusion: In conclusion, secondary bladder carcinoma metastasis from other organs presents a diagnostic dilemma and requires comprehensive evaluations. Healthcare professionals should consider metastasis malignancy in the differential diagnosis of high-grade urothelial lesions, especially in the absence of readily available clinical history of primary cancer. Keywords: Bladder cancer, secondary tumors, metastasis, differential diagnosis, primary cancer.